The Black Death, and The Dancing Mania - Hecker, J. F. C. (Justus Friedrich Carl), 1795-1850; Morley, Henry, 1822-1894; Babington, B. G. (Benjamin Guy), 1794-1866 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Black Death and The Dancing Mania" by J. F. C. Hecker is a historical account written in the early 19th century. This work delves into two significant historical phenomena: the catastrophic impact of the Black Death, a devastating plague that swept through Europe in the 14th century, and the dancing mania, a series of psychological episodes characterized by uncontrolled dancing. Hecker examines these events not only in a medical context but also through the lens of their effects on society, culture, and the human psyche. At the start of the text, the reader is introduced to an in-depth analysis of the Black Death, detailing its symptoms, causes, and societal consequences. Hecker describes the nature of the disease, emphasizing its rapid and deadly spread, corroborated by historical testimonies and accounts from witnesses such as Guy de Chauliac and Boccaccio. The opening chapters set the stage for a deeper exploration of how this plague altered the course of human history, prompting significant changes in public behavior, morality, and social structures during a time of overwhelming fear and uncertainty. Hecker aims to piece together these dramatic events to provide insights into the relationship between epidemics and the evolution of civilization. (This is an automatically generated summary.)
Release date is 1999-05-01
Transcribed from the 1888 Cassell & Company edition by Jane Duff, proofed by David Price
Keywords: Black Death; Chorea, Epidemic; Epidemics